Dinamika Hukum Adat: Eksistensi dan Validitas Kesepakatan Adat dalam Perkawinan Masyarakat Ammatoa Kajang - Andi Bau Malarangeng; Siardin Andi Djemma; Hardiyan; Budiyamin (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2026)
This study aims to analyze the existence of customary agreements in marriages among the Ammatoa Kajang indigenous people and the factors that influence them. The research method used is normative and empirical legal research with a qualitative descriptive approach. Data were obtained through interviews, field observations, and library studies of laws and regulations as well as customary law literature. The results of the study indicate that customary agreements in marriages among the Ammatoa Kajang indigenous people still exist and are implemented based on Pasang ri Kajang as a guideline for community life. Customary agreements regulate the stages of marriage, requirements for prospective brides and grooms, and obligations of both parties and are prioritized over state law provisions, particularly regarding age limits and marriage registration. The research findings indicate that there are still marriages that are legally valid according to custom but are not administratively registered. Factors that influence the existence of customary agreements include the lack of socialization of state law, the strength of Pasang ri Kajang, the existence of customary sanctions as a means of social control, and the value of siri (self-esteem) that is highly upheld by the community. The implications of this study indicate the need for harmonization between customary law (living law) and state law to achieve legal certainty without eliminating the cultural values ​​of indigenous communities